THE EFFECT OF DIGITAL LITERATURE ON STUDENTS' LEARNING INDEPENDENCE IN THE 2019 COVID SITUATION - Wahyuni Nurwasi’ah, Santa, Dadang Kurnia, Lina Novita, Elly Sukmanasa (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study is a quantitative study through a causal approach with the purpose of determining the effect of digital literacy on the results of students' learning autonomy in the 2019 COVID situation. This study was conducted to test the validity of the instrument using the formula Person Product Moment correlation and reliability test using Cronbach's Alpha formula. The sample in this study was 42 students of the Elementary School, which was obtained using the Taro Yamane formula. This quantitative research was continued with the requirements test of data analysis using the Normality, Homogeneity, and Linearity tests. The average value for the digital literacy variable is 84.73 and the average value for the learning independence variable is 78.29. The results showed that there was an effect of digital literacy on learning independence, which was indicated by the path coefficient (pxy) of 0.70. This shows the influence of digital literacy on learning independence, while the coefficient of determination (r2) is 0.49 or 49%. This means that the value of the influence of digital literacy on learning independence is 49%, through the regression equation Y =(10.49 + 0.8X). Based on the results of the research above, it can be concluded that there is a positive influence of digital literacy on the learning independence of students in the 2019 COVID situation.